Customized footwear for motion control to treat anterior knee pain among runners - Sadigursky,David (2017)
BACKGROUND: Street running is extremely popular worldwide. Despite its benefits, there is evidence that stressful physical activity contributes to the development of lesions on the patellofemoral joint, leading, to anterior knee pain. As an attempt to attain pain control and to improve performance, specific footwear is being developed, aiming to suit particular types of foot strike, and therefore to reduce the risk of injury. OBJECTIVE: To evaluate the effectiveness of the use of customized shoes, based on baropodometric test, for the remission of anterior knee pain among amateur street runners. METHODS: This is a cross-sectional study, using questionnaires based on anthropometric and anatomical data of the runner, type of training, individualized footwear based on baropodometric test and diagnosis of anterior knee pain. In total, 40 athletes were studied, which were divided into two groups: Group 1, with 19 athletes who wore specific shoes for their activity, according to the type of foot strike, and, Group 2, with 21 athletes who used neutral shoes, not prescribed by healthcare professionals. All athletes practiced at the same running field. RESULTS: Most of the athletes were female (70%), The pain remission had no overall statistically significant difference between the two groups. However, significant differences were found between groups A and B regarding the time of occurrence and the extent of AKP. CONCLUSION: The data analysis showed that the use of customized running shoes, based exclusively on baropodometric exams, does not reduce anterior knee pain in amateur street runners, which is consistent with current literature. The improvement of pain with customized shoes, when present, appeared to have a short duration of around three month.